2004
DOI: 10.1007/s00380-004-0779-3
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Patients with mild hypertensive heart disease and left ventricular outflow tract obstruction: treatment with angiotensin II antagonists

Abstract: The aim of this work was to investigate the association between homocysteine levels and coffee consumption in a sample of cardiovascular disease-free men and women. From May 2001 to December 2002, we randomly enrolled 1514 men and 1528 women, stratified by age and gender, from the greater area of Athens. Blood samples were collected in the fasting state. Among other investigated factors, dietary habits (including coffee consumption in ml per day, adjusted for 28% caffeine containment) were evaluated using a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They can decrease the severity of intraventricular obstruction and LVH. 18 Therefore, the antihypertensives regimen should be reviewed regularly based on the concurrent state of heart failure, severity of outflow obstruction, and whether the renal vessels are compressed. However, the definitive treatment would still be the ablation of the catecholamine-secreting neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…They can decrease the severity of intraventricular obstruction and LVH. 18 Therefore, the antihypertensives regimen should be reviewed regularly based on the concurrent state of heart failure, severity of outflow obstruction, and whether the renal vessels are compressed. However, the definitive treatment would still be the ablation of the catecholamine-secreting neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…32 In pressure overload model, early marked increase in angiotensin 2 type 1 (AT1) receptor density in the LV myocardium increases both plasma norepinephrine concentration and LV myocardial epinephrine content. 33 Nakagawa et al 34 have observed that AT1 receptor antagonist therapy is effective in LVOT gradient reduction. This management modality has also resulted in a regression of myocardial hypertrophy in mild hypertensive patients with LVH.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise can impact inflammatory cytokines. [ 14 ] Diet[ 15 16 ] including caffeine intake[ 17 18 ] can affect cytokine concentrations. Insomnia, common in people with schizophrenia, is associated with abnormal cytokine concentrations.…”
Section: Are Cytokine Abnormalities Independent Of Potential Confoundmentioning
confidence: 99%